Previous Archaeological Excavations along the 'Ostlänken' Railway Corridor 1965-2012: Four houses from the Early Iron Age - Swedish National Heritage Board, UV Öst (Uppsala University, 2020)
During the summer of 1191 the Swedish National Heritage Board UV East conducted archaeological investigation of settlement remain RAÄ 236 in Kallerstad due to the new road being built, Norra Länken.

445 features were discovered during the investigation. Most of them were part of four house constructions (House 1-4). Three of the houses (House 1-3) were elongated rectangular houses dated to Pre-Roman and Roman Iron Age. House 4 had a different construction than the others and was elongated with slightly bulged walls, dated to the Bronze Age.

The ZIP-file contains three shapefiles with information on trenches, ancient monuments, archaeological finds and other data from the archaeological survey, as well as one geo-referenced map (© Lantmäteriet i2014/00696) of the survey in GeoTIFF-format.

Riksantikvarieämbetet UV Öst utförde arkeologisk undersökning sommaren 1991 av boplatslämningar RAÄ 236 på stadsäga 928, Kallerstad. Undersökningen föranleddes av anläggandet av en ny väg, Norra Länken.

Vid undersökningen påträffades 445 anläggningar. De flesta ingick i fyra huskonstruktioner (Hus 1-4). Tre av husen (Hus 1-3) var långsträckta rektangulära hus daterade till förromersk och romersk järnålder. Hus 4 har en annan konstruktion än de övriga och är långsträckt med lätt utbuktade väggar, daterat till bronsåldern.

ZIP-filen innehåller data i form av tre shapefiler med information om eventuella schakt, påträffade forn- och kulturlämningar och fynd samt andra metadata från den arkeologiska utredningen, samt en georefererad karta (© Lantmäteriet i2014/00696) över utredningsområdet i GeoTIFF-format.
Tidigare arkeologiska undersökningar längs Ostlänken-korridoren 1965-2012: Fyra hus från äldsta järnålder
Keywords: finds; fynd; HISTORY; HISTORIA; Archaeology; Arkeologi; Fieldwork archive; Fieldwork archive